Effectiveness of Interactive Multimedia on Behaviour Change of Deaf Adolescent Girl About Vaginal Discharge at SLBN Pembina Samarinda - Hendriani, Dwi; Chifdillah, Nino Adib; Pramono, Joko Sapto; Sutrisno, Sutrisno (Universitas Aisyah Pringsewu, 2024)
Background: Deaf adolescent girl often faced limitations in accessing comprehensive reproductive health information. The issue put them at high risk for reproductive health issues like pathological vaginal discharge (leucorrhea). The study aimed to determine the effect of interactive multimedia education on improving knowledge, attitude, and behavior related to vaginal discharge among deaf adolescent girl at the Special Needs School (SLB) Negeri Pembina Samarinda.Methods: The reseqarch was a quantitative pre-experimental study using a one-group pretest-posttest design. The sampling technique used the total samling by 8 deaf high school students aged 15–20-year-old. The intervention was the provision of interactive multimedia education on leucorrhea. Data on knowledge, attitude, and behavior were collected using questionnaires before the intervention (pretest) and after the intervention (posttest). The effect F intervention was analyzed using the Wilcoxon test.Results: The number of participants with pathological leucorrhea status decreased significantly from 8 (100%) to 2 (25%) at posttest. Statistical analysis showed a significant difference between pretest and posttest scores for knowledge (?=0.016), attitude (?= 0.031), and practice (?=0.031).Conclusion: Interactive multimedia was an effective and appropriate health education media for deaf adolescent girl, significantly improving their knowledge, attitude, and hygiene behavior about leucorrhea.